2018
DOI: 10.5114/bta.2018.79968
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in the growth and chemical constituents of Anoectochilus formosanus Hayata grown under hydroponic conditions

Abstract: Anoectochilus formosanus Hayata is an important medicinal plant with various pharmaceutical properties. In this study, A. formosanus plants were hydroponically cultivated in different nutrient solutions to achieve enhanced biomass and secondary metabolites production. Three months-old A. formosanus plants were grown for 8 weeks under controlled environment in plastic pots containing Murashige and Skoog (MS), Nitrophoska Foliar (NF), Hydro Green (HG), or Hydro Bee (HB) media. Among 4 nutrient solutions tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…It has the effects of clearing heat, removing dampness, and detoxifying [ 10 ]. Modern pharmacological study has shown that Anoectochilus contains flavonoids, alkaloids, steroids, polysaccharides, volatile oils, terpenoids, and other chemical components [ 11 ]. Anoectochilus has been documented to have multiple biological effects previously, such as antioxidant [ 12 ] and liver protection effect [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has the effects of clearing heat, removing dampness, and detoxifying [ 10 ]. Modern pharmacological study has shown that Anoectochilus contains flavonoids, alkaloids, steroids, polysaccharides, volatile oils, terpenoids, and other chemical components [ 11 ]. Anoectochilus has been documented to have multiple biological effects previously, such as antioxidant [ 12 ] and liver protection effect [ 13 ].…”
Section: Introductionmentioning
confidence: 99%